Intestinal helminthes and/or Toxocara infection are unrelated to anti-HBs titers in seven-year-old children vaccinated at birth with recombinant hepatitis B vaccine Helmintos intestinais e/ou infecção por Toxocara não tem relação com títulos de anti-HBs em crianças de sete anos de idade vacinadas ao nascer com vacina recombinante para hepatite B - Marisa B.C.L. Monteiro; Roberta Fragoso; Silvio Foletto; Elenice M. Lemos; Fausto E.L. Pereira (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
The aim of this investigation was to evaluate the possible effect of nematode infection on anti-HBs antibody levels in the serum of seven-year-old schoolchildren vaccinated at birth with the recombinant hepatitis B vaccine. Anti-HBs and anti HBc antibodies were evaluated in the sera of 100 schoolchildren with at least one intestinal nematode and/or a positive serological reaction for anti-Toxocara antibodies and in 95 schoolchildren without intestinal helminthiasis or serum anti-Toxocara antibodies. Both groups were from public elementary schools located on the urban periphery of Vitória, ES, Brazil. Among these 195 children, the median anti-HBs antibody titer was 31.3IU/ml and the frequency of titers less than 10IU/ml was 33.8% (95% CI: 27.1-40.4%). There were no significant differences between the medians of anti-HBs titers or the frequency of titers less than 10IU/ml between the groups with or without helminthes (29.5 and 32.9IU/ml and 33 and 34.7%, respectively; p>0.05). Even when the children with intestinal nematodes and/or anti-Toxocara antibodies and with blood eosinophil counts over 600/mm³ were compared with children without infection from intestinal nematodes and without anti-Toxocara antibodies, with blood eosinophil counts less than 400 eosinophils/mm³, these differences were not significant. None of the children presented anti-HBc antibodies. In conclusion, infections with intestinal nematodes and/or the presence of anti-Toxocara antibodies did not interfere with the anti-HBs antibody titers in seven-year-old children vaccinated at birth with the recombinant hepatitis B vaccine. O objetivo dessa investigação foi avaliar um possível efeito de infecções por nematóides sobre os níveis de anticorpos anti-HBs no soro de escolares de sete anos de idade, vacinados ao nascer com a vacina recombinante para hepatite B. Anticorpos anti-HBs e anti-HBc foram avaliados no soro de 100 escolares portadores de pelo menos um nematóide intestinal e/ou uma reação sorológica positiva para anticorpos anti-Toxocara e ...